Panax notoginseng saponins ameliorate cisplatin‐induced mitochondrial injury via the HIF‐1α/mitochondria/ROS pathway - Qingqing Li; Xueyan Liang; Yufang Yang; Xian Zeng; Xiaobin Zhong; Chun Huang (FEBS Open Bio)
Cisplatin is a major antineoplastic drug that is used to treat solid tumors, but its use is restricted by its nephrotoxicity. Such cisplatin‐induced nephrotoxicity (CIN) is believed to occur primarily through mitochondrial damage and reactive oxygen species (ROS) generation. Our previous studies have indicated that Panax notoginseng saponins (PNSs) mitigate CIN by enhancing hypoxia‐inducible factor 1α (HIF‐1α)‐induced mitochondrial autophagy. In this study, the role of the HIF‐1α/mitochondria/ROS pathway in PNSs protection against CIN was investigated using a rat model. A CIN model was generated by giving rats intraperitoneal injections with cisplatin (a single dose) and then treating them with or without 2‐methoxyestradiol (HIF‐1α inhibitor) and PNSs. We then measured ROS levels, superoxide dismutase, glutathione, catalase malondialdehyde and nitric oxide (to evaluate oxidative stress) and ATP, mitochondrial membrane potential and mitochondrial permeability transition pore opening (to evaluate mitochondrial function) in kidneys at different time points. We observed that PNSs remarkably reduced the levels of ROS, malondialdehyde and nitric oxide, as well as the opening of mitochondrial permeability transition pore, which is increased by cisplatin and further increased by HIF‐1α inhibition. In addition, PNSs increased the levels of superoxide dismutase, catalase and glutathione, as well as ATP and mitochondrial membrane potential in renal tissues; these are all reduced by cisplatin and further reduced by HIF‐1α inhibition. In conclusion, we demonstrate here that PNSs protects against mitochondrial damage induced by cisplatin through HIF‐1α/mitochondria/ROS.